2021
DOI: 10.1001/jamanetworkopen.2020.34878
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Unintentional Fatal and Nonfatal Emergency Medical Services–Attended Opioid Overdoses During the COVID-19 Pandemic in Philadelphia

Abstract: Non-Hispanic White individuals Non-Hispanic Black individuals Hispanic individuals a Period C indicates period of stay-at-home order, which began on March 23, 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 5 publications
0
81
3
Order By: Relevance
“… Patient experiences ( n = 1) Krawczyk et al [ 26 ] (International) Qualitative 300 posts of Reddit users related to COVID-19 and opioid used Concerns over less in-person access to OUD treatment facilities, COVID-19 testing treatment requirements and exposure to COVID were reported as an influence on motivation to seek treatment. Patient outcomes ( n = 5, 33%) Overdose (n = 3) Khatri et al [ 27 ] (U.S./Pennsylvania) Retrospective Philadelphia Dep Health Substance Use Dashboard and Medical Examiner’s Office Data African Americans comprised 80% of overdose ED visits post-pandemic, compared to 63% pre-pandemic. Ochalek et al [ 28 ] (U.S./Virginia) Retrospective Electronic medical record of Virginia Commonwealth University During the pandemic, 2.5 patients were seen per day in the emergency department with opioid overdose, compared to 1.4 patients per day pre-pandemic.…”
Section: Resultsmentioning
confidence: 99%
“… Patient experiences ( n = 1) Krawczyk et al [ 26 ] (International) Qualitative 300 posts of Reddit users related to COVID-19 and opioid used Concerns over less in-person access to OUD treatment facilities, COVID-19 testing treatment requirements and exposure to COVID were reported as an influence on motivation to seek treatment. Patient outcomes ( n = 5, 33%) Overdose (n = 3) Khatri et al [ 27 ] (U.S./Pennsylvania) Retrospective Philadelphia Dep Health Substance Use Dashboard and Medical Examiner’s Office Data African Americans comprised 80% of overdose ED visits post-pandemic, compared to 63% pre-pandemic. Ochalek et al [ 28 ] (U.S./Virginia) Retrospective Electronic medical record of Virginia Commonwealth University During the pandemic, 2.5 patients were seen per day in the emergency department with opioid overdose, compared to 1.4 patients per day pre-pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Third, our sample had low racial and ethnic diversity. Because Black, Indigenous, and People of Color disproportionately suffered from death and other complications of SARS-COV-2 [51] and also disproportionately experience opioid-related harms, including during the pandemic [52], future work should explore intersecting vulnerabilities of SUD, hospitalization, and acute crises like pandemics in this population. Fourth, it is possible that our research does not encompass all challenges faced by marginalized patients in healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Published research in the past year discussed the rising prevalence of substance use around the world [ 3 ▪ , 4 ▪ , 6 ▪ , 7 ▪▪ , 8 ▪ ] and suggested that individuals who use substances may be at an increased risk for COVID-19 [ 32 ▪ , 33 ▪▪ ]. Implementation of stay-at-home orders were associated with increased overdose rates [ 19 ▪ 21 ▪ ]. In addition to differences in substance use and overdose rates, systematic and individual barriers to care increased because of pandemic mitigation efforts [ 11 ▪ ] including closures/reductions in treatment or management services [ 12 ▪ , 27 ▪ ] and difficulty finding out about/unfamiliarity with available resources [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opioid overdose-related runs by emergency medical services also rose in Kentucky after the SAHO was implemented [ 20 ▪ ]. The SAHO in Philadelphia was associated with an increase in the mean number of unintentional fatal opioid overdoses per month for non-Hispanic Black people [ 21 ▪ ]. In New Zealand, a significant increase was observed in the percentage of patients arriving to one emergency department with an overdose in the mandated lockdown compared with before the lockdown [ 22 ▪▪ ].…”
Section: Overdose Riskmentioning
confidence: 99%